Ixeridium malingheense (Asteraceae), a new species from southwestern Guizhou, China - Xu, Qin; Yang, Long; An, Mingtai; Yu, Jianghong; Liu, Feng; Li, Zhi (Phytotaxa, 2024)
A new Asteraceae species, Ixeridium malingheense Z.Li & Q.Xu sp. nov., from Xingyi City, south-western Guizhou, China, is described and illustrated based on morphological and molecular analyses. Compared with the other species of the genus, the species is most similar to I. yunnanense in a small stature, linear-lanceolate stem leaves, and short phyllaries. However, it is easily distinguished from the latter by its smaller basal leaves 18–34 × 5–13 mm (vs. 10–25 × 5 mm), spatulate or long-spatulate (vs. elliptic, lanceolate, or oblanceolate), petioles ca. 30–55 mm (vs. 10 mm to absent), outer phyllaries 1-seriate (vs. 2-seriate, unequal), achenes smaller 2.0–3.0 × 0.5–1.0 mm (vs. 3.2 × 0.6 mm), and a flowering period of March to May (vs. June). Molecular phylogenetic analyses based on nuclear ITS sequence data determined the systematic position of I. malingheense in Ixeridium.